Manipulating plant microbiomes in the field: Native mycorrhizae advance plant succession and improve native plant restoration. Issue 8 (5th October 2021) - Koziol, Liz; Bauer, Jonathan T.; Duell, Eric B.; Hickman, Karen; House, Geoffrey L.; Schultz, Peggy A.; Tipton, Alice G.; Wilson, Gail W. T.; Bever, James D.
Abstract: The plant microbiome is critical to plant health and is degraded with anthropogenic disturbance. However, the value of re‐establishing the native microbiome is rarely considered in ecological restoration. Arbuscular mycorrhizal (AM) fungi are particularly important microbiome components, as they associate with most plants, and later successional grassland plants are strongly responsive to native AM fungi. With five separate sites across the United States, we inoculated mid‐ and late successional plant seedlings with one of three types of native microbiome amendments: (a) whole rhizosphere soil collected from local old‐growth, undisturbed grassland communities in Illinois, Kansas or Oklahoma, (b) laboratory cultured AM fungi from these same old‐growth grassland sites or (c) no microbiome amendment. We also seeded each restoration with a diverse native seed mixture. Plant establishment and growth was followed for three growing seasons. The reintroduction of soil microbiome from native ecosystems improved restoration establishment. Including only native arbuscular mycorrhizal fungal communities produced similar improvements in plant establishment as what was found with whole soil microbiome amendment. These findings were robust across plant functional groups. Inoculated plants (amended with either AM fungi or whole soil) also grew more leaves and were generally taller during the three growing seasons. Synthesis and applications . Our research shows that mycorrhizal fungi can accelerate plant succession and that the reintroduction of both whole soil and laboratory cultivated native mycorrhizal fungi can be used as tools to improve native plant restoration following anthropogenic disturbance. Abstract : Our research shows that mycorrhizal fungi can accelerate plant succession and that the reintroduction of both whole soil and laboratory cultivated native mycorrhizal fungi can be used as tools to improve native plant restoration following anthropogenic disturbance.